Surgical treatment of displaced intra-articular calcaneal fracture using a single small lateral approach - Mostafa, Mohamed F. (Springer Milan, 2010)
The objective of this study was to evaluate the outcome of semi-open reduction and minimal internal fixation through a single small lateral approach as a minimally invasive technique for treatment of displaced intra-articular calcaneal fractures. This prospective study was conducted on eighteen patients (16 men and 2 women). The average age was 37.7 (22–55). The most common cause of injury was a fall from height in fourteen patients. Patients were operated on within a mean time of 4.8 days of admission (1–11 days) and were followed up for an average period of 24.1 months (6–39 months). Patients were evaluated clinically using the Creighton-Nebraska Heath Foundation Assessment score of Crosby and Fitzgibbons (J Bone Joint Surg (Am) 72-A:852–859, 1990). The scoring system proposed by Knirk and Jupiter was used for radiological assessment of the posterior subtalar joint (Knirk and Jupiter in J Bone Joint Surg (Am) 68-A: 647–659, 1986). The skin incision healed in all cases without necrosis, infection, or sural nerve injury. All fractures healed after an average of 8 weeks (7–10 weeks), and patients returned to the routine daily activities after an average time of 4.3 months (3–7 months). In conclusion, semi-open reduction and minimal internal fixation through a small lateral approach is an effective treatment for carefully selected cases of displaced intra-articular calcaneal fractures.